Pro-poor growth: The Asian experience - Nanak Kakwani; Hyun H. Son (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper looks into the interrelation between economic growth, inequality, and poverty. Using the notion of pro-poor growth, this study examines to what extent the poor benefit from economic growth. First, various approaches to defining and measuring pro-poor growth are scrutinized using a variety of criteria. It is argued that the satisfaction of a monotonicity axiom is a key criterion for measuring pro-poor growth. The monotonicity axiom sets out a condition that the proportional reduction in poverty is monotonically an increasing function of the pro-poor growth measure. This paper proposes a pro-poor growth measure that satisfies the monotonicity criterion. This measure is called the `poverty equivalent growth rate', which takes into account both the magnitude of growth and how the benefits of the growth are distributed to the poor and the non-poor. As the new measure satisfies the criterion of monotonicity, it is indicative that to achieve a rapid poverty reduction, the poverty equivalent growth rate ought to be maximized rather than the actual growth rate. The methodology developed in the paper is then applied to Asian countries, including the Republic of Korea, Thailand, and Vietnam.
Keywords: O40; I32; D31; 330; economic growth; poverty; inequality; Wirtschaftswachstum; Einkommensverteilung; Armut; Armutspolitik; Asien